A structured, microsurgical training curriculum improves the outcome in lower extremity reconstruction free flap residency training: the Ludwigshafen Concept - Böcker, Arne Hendrik; Kornmann, Jonas; Xiong, Lingyun; Harhaus-Wähner, Leila; Aman, Martin; Köpple, Christoph; Fischer, Sebastian; Will-Marks, Patrick; Kneser, Ulrich; Hirche, Christoph (Journal of reconstructive microsurgery, 2021)
Background Risk stratification, economic pressure, and a flat learning curve make the realization and development of proper microsurgical skills and competences a challenging task in the daily clinical practice. In previous studies, we were able to show that microsurgical procedures, e.g., free flaps and replantations, are safe training procedures and teachable in daily clinical practice in view of certain issues of risk stratification. The present study aims to evaluate further improvements in terms of safety and complication rates for free flaps as a training procedure after introduction and continuous implementation of a structured in-house training curriculum for microsurgical skills and competences and a 24-hour free accessible microsurgical training facility for the plastic surgery resident. Methods This retrospective comparative cohort study was conducted to review whether microsurgical skills for free flaps to the lower extremity can further be improved after implementation of the curriculum and a 24-hour accessible training facility. Therefore, we compared cohort A before (2009-2012) and B after (2014-2017) implementation. Patient demographics, procedural characteristics, and outcome parameters for free tissue transfer of the lower extremity were evaluated. Results The comparison of both cohorts showed a significantly reduced postoperative complication rate for cohort B (p <0.05). Furthermore, operation time was shorter, and the hospital stay could be significantly decreased (p <0.01). Workhorse flaps for plastic surgical training were the anterior lateral thigh (ALT) flap or the musculus latissimus dorsi (LD) flap. However, even more complex procedures with arteriovenous loops could be safely performed by plastic surgery residents under the supervision of the senior surgeon in exceptional cases. Conclusion The implementation of a regularly held, microsurgical in-house training curriculum with 24-hour accessible training facility improves procedural and outcome parameters for free flaps to the lower extremity for surgical residents and is an elementary part of skills and competency training. However, risk stratification, repeated surgical exposure, expertise, and institutional infrastructures are essential and must be taken into consideration.
Online veröffentlicht: 19. November 2020
Gesehen am 05.04.2024